Calculation of electromagnetic force and temperature distribution of amorphous transformers in different operating modes by finite element method - Hong Hai Pham; Bao Doan Thanh (CTU Journal of Innovation and Sustainable Development)
The study used the Finite element method (FEM) by ANSYS 3D software to calculate the distribution of electromagnetic force (EMF) and temperature on the high voltage and low voltage windings (HLVWs) of the amorphous steel core 3 phase transformer (ASCT) which has a power of 1000kVA –22/0.4kV under different load cases: No load, full load and short circuit (SC). The obtained results show the exact temperature distribution and location where the highest temperature is found on the HLVWs of ASCT. From the analysis of the temperature distribution on the HLVWs, it is shown that when the transformer falls into an SC fault, it causes the greatest EMF and thermodynamic force, causing extremely heavy consequences for the transformers. The obtained results help designers, manufacturers, and operators have the most suitable options to improve strength of SC and increase the life of the transformer.